A novel member of the let-7 microRNA family is associated with developmental transitions in filarial nematode parasites - Winter, Alan D.; Gillan, Victoria; Maitland, Kirsty; Emes, Richard D.; Roberts, BBrett; McCormack, Gillian; Weir, William; Prostaio, Anna V.; Holroyd, Nancy; Berriman, Matthew; Britton, Collette; Devaney, Eileen (BioMed Central, 2015)
Background: Filarial nematodes are important pathogens in the tropics transmitted to humans via the bite of blood sucking arthropod vectors. The molecular mechanisms underpinning survival and differentiation of these parasites following transmission are poorly understood. microRNAs are small non-coding RNA molecules that regulate target mRNAs and we set out to investigate whether they play a role in the infection event. Results: microRNAs differentially expressed during the early post-infective stages of Brugia pahangi L3 were identified by microarray analysis. One of these, bpa-miR-5364, was selected for further study as it is upregulated ~12-fold at 24 hours post-infection, is specific to clade III nematodes, and is a novel member of the let-7 family, which are known to have key developmental functions in the free-living nematode Caenorhabditis elegans. Predicted mRNA targets of bpa-miR-5364 were identified using bioinformatics and comparative genomics approaches that relied on the conservation of miR-5364 binding sites in the orthologous mRNAs of other filarial nematodes. Finally, we confirmed the interaction between bpa-miR-5364 and three of its predicted targets using a dual luciferase assay. Conclusions: These data provide new insight into the molecular mechanisms underpinning the transmission of third stage larvae of filarial nematodes from vector to mammal. This study is the first to identify parasitic nematode mRNAs that are verified targets of specific microRNAs and demonstrates that post-transcriptional control of gene expression via stage-specific expression of microRNAs may be important in the success of filarial infection.